IPE and European Integration: Applying Karl Polanyi's 'the Great Transformation' - Copeland, Paul (Conference Papers – International Studies Association, 2008)
European integration is usually studied within the realms of comparative politics. The multitude of empirical studies concerning the topic have been well suited to its numerous methodologies and analytical frameworks. Comparative politics however, usually ignores the question of why European integration has both progressively deepened and widened during the last thirty years. Therefore there is a distinct absence of how developments in the global political economy determine European integration. Such an approach fails to address the issues of power and constraint within the global economy. We would therefore expect the process to be examined within international political economy, yet there has been a relative neglect of European integration within IPE as it considers the process to be a mere regional response to global developments. This paper argues that European integration is a more complex process than IPE has considered and addresses its relative neglect by applying Polanyiâs 'the Great Transformation'. Firstly, this paper argues that existing comparative politics and IPE approaches to European integration have a number of shortcomings which limits their application. Secondly, to address these limitations this paper applies 'the Great Transformation' to European integration and argues there to be strong parallels between Polanyiâs theory and the process. Thirdly, the paper argues that European integration is much more than a simplistic regional response to globalisation. European integration has been a contradictory process oscillating between neoliberalism and the European Social model. This highlights not just the contradictions of European integration, but also what Polanyi termed the âmarket societyâ. ..PAT.-Unpublished Manuscript
Political Science; International Relations
Keywords: European integration; comparative government; globalization; international economic relations; international political economy; neoliberalism

Is Market Liberalization Pathological? Debating the Causes of Corruption in Chinese Banking - Eaton, Sarah (Conference Papers – International Studies Association, 2008)
Neoclassical economists posit that the freeing of market forces will lead, ceteris paribus, to a reduction in levels of corruption. There are several mechanisms through which this hypothesized effect is channeled, the most important of which is competition pressure brought by the entry of foreign firms into the domestic market. The empirical leverage of this approach has been strongly challenged by events of recent years. In China and Russia, market liberalization has not had the expected effects: corruption has exploded alongside market opening. Why? The view among many economists is that the benefits of market opening were stymied by the political logic governing the process of reforms (e.g. cronyism in privatization, trade policy protection of inefficient domestic firms et cetera). The Polanyi-inspired counter-claim is that reform-era corruption is itself an effect of the disembedding of the political economy. My research on corruption in the Chinese banking industry lends empirical insight to the debate. Because the Chinese market is variegated, with some firms being much more exposed to competition than others, there is the opportunity to test these explanatory variables against corruption levels in different segments of the market. On the basis of original fieldwork conducted in China, this paper suggests that the neoclassical economists faith in market opening as an anticorruption mechanism is unwarranted. ..PAT.-Unpublished Manuscript
Political Science
Keywords: China; banking industry; corruption; disembeddedness; ethics; market liberalization; white collar crimes

Reconfiguring the Terrain of Cultural Governance in Mexico: The Role of the Mexican Film Community in the Era of Neoliberal Globalization - Busmann, Nadine (Conference Papers – International Studies Association, 2007)
Reconfiguring the Terrain of Cultural Governance in Mexico: The Role of the Mexican Film Community in the Era of Neoliberal Globalization Embracing the dominant neoliberal project, many Mexican elites have prioritized economic growth and market logics over broader social goals. The unleashing of market forces globally,and the adoption of neoliberal policies nationally have had a significant impact on local communities and national culture in Mexico. Focusing on Mexican cultural production, this paper explores the shifting terrain of political struggle in the Mexican film industry. One of the central concerns of this paper is what processes and on what authority the imagined political community in Mexico is constructed, reconstructed, and reproduced in the current era of neoliberal globalization. Historically, political contestation among political, cultural and business elites has been central to the perpetuation of the national cultural project, in this paper, it is argued that the changing political landscape in Mexico has created new conditions for contestation providing sites for previously marginalized forces to challenge the hegemony of neoliberalism.Conceptualising neoliberal globalization and its application by Mexican elites in Polanyian terms?as a double movement?the paper examines the consolidation of the Mexican film coalition as a counter-movement, driven by cultural elites, which emerged to contest the hegemony of market driven politics. In this regard the paper analyzes the ideological and material foundations of this movement. Further, it examines the coalition´s efforts to create a social base from which to reshape the state´s politico-cultural agenda to ensure the survival of an indigenous film industry, thus providing (sub)national identities with an image and voice in the face of globalizing forces. It suggests that organic intellectuals built collective political agency upon the conviction that neoliberal globalization is to be resisted insofar as it subjects the nation to transnational?and hence alien?cultural, political and economic forces. Lastly, it challenges the assumption that in challenging the hegemony of neoliberalism the film community is anti-capitalist. As the evidence will reveal the motivating factors and ideological foundations driving the efforts of the film community are much more complex. ..PAT.-Unpublished Manuscript
Political Science
Keywords: Mexico; cultural production; elite (social sciences); globalization; international studies; neoliberalism; social goals

Searching for the Theory of Practice behind the WTO's Commodification Mandate - Göpel, Maja (Conference Papers – International Studies Association, 2007)
When trying to understand the origins of the collapse of nineteenth-century civilization, Karl Polanyi identified a Great Transformation into a "starkly utopian" Self-Regulating Market (SRM). This shift entailed 2 elements: a wide-ranging re-regulation of organization and control of production processes, and the development of economic liberalism as a body of thought that provided justification of a new set of public policies that facilitated a transformation of land (nature), labor (people), and capital (money) into "fictitious commodities." Even though these factors have not originally been produced for sale, they are now organized by purchase-logics and their value determined by market signals. Philosophy of praxis approaches point out that this process of transformation is never complete. Neither the ?discovery? of new commodities, nor the expansion of market logics are natural, but the outcome of socio-political struggles. New agreements of the World Trade Organization for example render ever more elements of social life and nature as ?trade related? and under its auspices the next great commodification wave unfolds. This paper traces which type of knowledge publicly justifies the resulting floods these policies release before comparing it with concrete negotiated outcomes and their impacts. The final discussion will circle the question to which extent ?objective? science influences policy-making - or if subjective selection of sciences supports policy-selling. ..PAT.-Unpublished Manuscript
Political Science
Keywords: World Trade Organization (WTO); commodification; ideal types; institutionalism; international trade; manufacturing processes; methodology; policy sciences; trade regulation

The Intellectual Commons vs Intellectual Property: Marxian and Polanyian Perspectives on Intellectual Capital, including Remarks on Primitive Accumulation - Jessop, Bob (Conference Papers – International Studies Association, 2007)
This paper explores the increasing significance of intellectual property rights for the appropriation of surplus value in capitalism. Building on Marx's analysis of the value form and extending it to the commodification of knowledge, it develops a Marxian critique of informational capitalism based on the basic categories of value theory; inter alia, this looks at the commodification of knowledge from the viewpoint of commodity fetishism, the enclosure of traditional knowledge, the formal subsumption of intellectual labour, the real subsumption of intellectual labour, and the role of intellectual property rights as a contradictory means to support the average rate of profit for firms specializing in immaterial production (whilst enabling them to appropriate monopoly profits). The second part of the paper inquires whether these arguments lend support to a Polanyian interpretation of knowledge as a fictitious commodity. On the basis of the arguments already deployed, plus further arguments, it is suggested that knowledge can function as a non-commodity, a quasi-commodity, a fictitious commodity, a real commodity, and as fictive capital. This has interesting implications for the concepts of primitive accumulation and accumulation through dispossession. ..PAT.-Unpublished Manuscript
Political Science
Keywords: Marxist philosophy; capitalism; commodification; intellectual property; political doctrines

What's Left in the City? What's Right in the Hinterland?: Urban Political Economy in Contemporary Latin America - Goldfrank, Benjamin; Schrank, Andrew (Conference Papers – American Political Science Association, 2006)
This paper accounts for the initial divergence and subsequent convergence of two types of urban political economy-neoliberal and socialist-in late twentieth and early twenty first century Latin America. Part 1 identifies the ideological differences between the two types of city as well as their implications for public policy. While neoliberal cities prioritize accumulation, and therefore use tax breaks, regulatory rollbacks, and the repression of organized labor to attract and retain foreign direct investment, their socialist rivals prioritize distribution, and therefore use social funds,microcredit arrangements, and participatory institutions to employ and empower their citizens. Part 2 treats the emergence of municipal neoliberalism as a secondary city or hinterland reaction to the growth of urban primacy or bias in the 1960s and 1970s. While industrial interests in population centers like Mexico City and São Paulo reaped the rewards of import-substituting industrialization, and therefore organized to defend their gains, their agro-commercial rivals paid a high price for tariffs and foreign exchange controls, and therefore deployed free trade zones (and similar incentives) in places like Chihuahua and Salvador to offset or compensate for the growth of urban primacy. Part 3 traces the origins of municipal socialism to the breakdown of ISI and the accompanying debt crisis in the late twentieth century. While neoliberal municipalities had already embraced the world market, and therefore welcomed structural adjustment at the national level, their socialist rivals feared globalization, and responded with a variety of compensatory measures of their own designed to increase the "social wage" not only in Mexico City and São Paulo but in other major cities like Caracas, Montevideo, and Lima. And, finally, Part 4 concludes by offering a Polanyian interpretation of the seemingly odd convergence of neoliberal and socialist municipalities today-suggesting that, whatever their ideological preferences, municipal authorities must balance accumulation with distribution if they are to survive and prosper in a globalized world. ..PAT.-Unpublished Manuscript
Political Science
Keywords: EPZ; Latin America; Latin America - politics & government; cities & towns; foreign investments; local politics; neoliberalism; participatory budgeting; political planning; socialism

Antecedents of Resistance: Populism and the Possibilities for Democratic Globalization - Plante, David J.; Niemi, William L. (2004)
Globalization is often portrayed as a new and unique phenomenon to our times. However, the dependence of American society upon global markets is not new. American Populists of the 19th century faced a similar matrix of political economic constraints. The Populists faced such challenges as the expansion of international trade, a deflationary international monetary order, integrating global capital markets, dependence on credit, and a political system unable to effectively regulate economic activity to public ends. In short, they responded to a system that from their perspective emphasized corporate profits at the expense of democracy. The Populists goal was to create a more democratic political economy in the face of these constraints. Today globalism has been countered by a diverse series of previously unconnected social movements. This paper argues that these movements are part of a rich tradition of democratic responses to the dislocations resulting from attempts to internationalize and commodify all social relations. As such, these 19th century movements offer instruction in the confrontation between democracy and capitalism in its latest iteration. For example, one important continuity between resistance to globalism today, is the use of democratized traditions of moral economy arguments to confront developing inequalities. Successful fair trade alternatives to free trade similarly depend upon moral economy arguments. Despite the inequalities resulting from globalization, challenges from the democratic promise have endured.
Political Science
Keywords: capital market; capitalism; corporate profits; democracy; fair; globalism; globalization; international trade; monetary policy; populism; trade

Disembedded Liberalism: Why global - Borowiak, Craig (2004)
Bringing together democratic theory and international political economy literatures, I begin with the thesis that economic globalization is undermining the embedded liberalism of the post WWII era. Embodied in the Keynsian welfare state, embedded liberalism held out democratic avenues for disaffected groups to hold political actors responsible for suffering induced by market forces. Transformations in the global economy, however, constrain the options available to governments and curtail avenues of democratic accountability. Some have argued that the market itself can provide an adequate alternative. This view is deeply flawed. Drawing from the economic theory of Hayek and Friedman, I discuss how markets can operate as accountability mechanisms. I then turn to Karl Polanyi to discuss how markets that become disembedded from social contexts induce severe consequences for society and the environment. These consequences exceed what markets alone can account for. What’s more, as Habermas has observed, the system logic of markets is incompatible with the deliberative contexts in which democratic decision-making takes place. To propose markets as the solution to democratic deficits is to miss the point that it is the substitution of markets for social regulation that generates many of the problems in the first place. It is also to ignore the ways markets undermine the very spaces in which legitimate solutions can be determined. Somehow the effects of market accountability need to be accounted for. For this, there can be no substitute for forms of democratic deliberation that are themselves not reducible to market pressures.
Political Science
Keywords: economics; globalization; international relations; liberalism; markets

How likely is a Post-Smithist 21st Century? - Cole, Constance H. (2004)
The current understanding of U.S. hegemony rests on the assumptions of neoclassical theories of both the state and the market. While the service-dominated economy is considered post- Fordist, the rhetoric of the state focuses on institutions of democracy. To what extent is our understanding of democracy dependent on the prior assumptions that the economy is ‘free’? If we reexamine the assumptions about the links between state and economy, drawing on the work of Gramsci, and Polanyi the necessary link between state and economy assumed in our current neoclassical theory looks quite different. The thesis of this research is that hegemonic ideologies of the relationship of state and market reinforce the interests of the commercial class at the expense of any meaningful representation of the working classes. Reconceptualizing the links between state and market in terms of an economics subordinate to social relations beyond those of commercial interests indicates the possibilities of a ‘post- Smithist’ understanding of both the imperfections of neoclassical market theories, and of the narrowness of institutional analyses.
Political Science; International Studies
Keywords: Fordism; Smithism; United States; democracy; economics; economy; hegemony; international; political; post; theory

The Culture War Goes Global: 'Family Values' and the Shape of U.S. Foreign Policy - Kline, Scott (2004)
Examines a neoconservative-religious right nexus that has emerged in and around the Bush White House. Discussion on the work of Karl Polanyi to examine a paradoxical tension that exists between U.S. nationalism and the promotion of a free-market economy; Family values nationalism and free market capitalism; Proposed two areas of critique that have been influenced by the work of Christian realists.
Politcal Science
Keywords: United States; capitalism; economic policy; free enterprise; international studies; nationalism; neo-conservatism; political doctrines

The Reconfiguration of the State under Economic Conditionality and the Creation of Hollow Democracies ? With Illustrations from Zambia - Lloyd, Peter (2004)
This paper will explore the linkages and contradictions between the promotion of democracy and the application of economic and political conditionality in Southern Africa, with particular reference to Zambia. Many electoral democracies have emerged in Africa in the last decade in conjunction with and partially as a consequence of the conditions applied to loans by bilateral and multilateral donors. It will be argued that the process of conditionality and the neoliberal policies applied actually inhibit the emergence of substantive democracy and present a threat to the consolidation and longevity of even minimal forms of liberal democracy. The conditions applied to aid represent an attempt to reconfigure the activities, capacity and capabilities of the state. Most significantly, they involve the imposition of a neoliberal economic model which is seen as technically necessary to tackle economic crisis and which due to the leverage offered donors by the indebtedness of recipient countries is uncontestable, yet require active state intervention to achieve (Polanyi’s insight that the creation of self regulating markets require regulatory state activity). A major area of state policy is thus placed beyond accountability to the electorate of the recipient country; this is also true of many aspects of political and social policy. The process of negotiation between the International Financial Institutions and representatives of countries (most often the President and a small group of politicians and advisors from the finance ministry) also promotes a concentration of power within the state as representatives must be able to adopt positions on the behalf of their country and enact agreed policies from the top down. Conditionality thus involves a reduction in the democratic accountability of the state in three ways: Firstly, as political authority shifts upwards to the international sphere, to the IFIs and donor community; secondly as power is centralised within the presidency and finance ministry; thirdly, the scope of democracy is limited as liberalisation and the strict separation of politics and economics are enforced, placing many elements of economic life beyond the reach of democratic institutions. Applying this framework to Zambia, it will be argued that consequently a very limited and hollow form of democracy where most of the important political and economic processes affecting people’s lives are unaccountable to them has been created, and that increasing disillusionment and political volatility are ensuing, possibly representing a threat to even this minimal democracy.
Political Science
Keywords: South Africa; democracy; economics; international studies; political doctrines; political science

The Great Transformation II: Human Rights Leapfrogging in the Era of Globalization - Howard-Hassmann, Rhoda (2003)
Whether globalization will result in improvement or deterioration in protection of human rights is not a matter that can be observed in the short term. Globalization is, in effect, the second ‘great transformation’ (Polanyi) spreading capitalism over the entire world. In consequence, many of its short-term effects will be negative. Nevertheless, its medium and long-term effects may well be positive, as it impels social changes that will result in greater moves to democracy, economic redistribution, the rule of law, and promotion of civil and political rights. Capitalism is a necessary, though hardly sufficient condition for democracy: democracy is the best, though not the inevitable, political system to protect human rights. This does not mean that the non-Western world will follow the exact same path to protection of human rights that the Western world followed. The West had a singular advantage: it was not expected to protect human rights during its own era of economic expansion. Thus, the West was able to practice slavery, expel surplus populations, and colonize other parts of the world. Genocide and ethnic cleaning were permissible state activities. The non-Western world does not enjoy the advantage of human rights lawlessness. It does, however, enjoy other advantages occasioned by the presence of human rights. There is a global communications network and a global pro-human rights social movement. There is also the movement to global governance. Finally, and paradoxically, there is the global social movement against globalization, which forces some reflection upon its deleterious consequences. Thus, the non-Western world benefits from geographical and chronological human rights ‘leapfrogging’. This, along with the social changes that global capitalism and industrialism may impel, may mean that the medium and long-term consequences of globalization are positive for human rights.
Political Science
Keywords: capitalism; democracy; globalization; human rights; human rights advocacy; social change

Place, Capitalism, and Democratic Efficacy - Kogl, Alexandra (2002)
Political Science
Keywords: DELEUZE; Gilles; capitalism; democracy; democratic; economy; efficacy; empire; place; political; theory

The Great Transformation at Sea: Fictitious Commodities and the Crisis of Marine Fisheries - Ziegelmayer, Eric (2002)
Challenging contemporary debates concerning the regulation of ocean fisheries, this paper deploys theoretical insights developed by Karl Polanyi. In The Great Transformation, Polanyi documented the consequences of the establishment of market economy upon European society, and thereby upon the entire planet. The concept of the self-regulating market, according to Polanyi was based on three "commodity fictions" of land, labor and money; the extension of this concept to all of the economic institutions of society he called "market utopianism." This paper extends Polanyi’s fictitious commodity thesis to the living resources of the ocean and argues that the roots of the contemporary problems of the world’s fisheries originate in the exposure of nature to a market economy. Concerned with the future governance of ocean resources and democracy in fishery regulation, the paper examines the globalization of the fishing industry in comparative and historical perspective to illuminate the validity of Polanyi’s theory. While there can be no final agreement as to the constitution of "good society", a useful starting point for debate is provided by the work of Karl Polanyi. A good society, he claims, is a society capable of producing goods, and a necessary condition of life in such a society is that human beings and nature are not treated as commodities
Political Science
Keywords: capitalism; democracy; economy; fictitious commodities; fisheries; fishery policy; political; property; rights; saltwater fishing

The utopian character of the counter-movements : reading Karl Polanyi in the twenty-first century - Rondelez, Pieter (13th Global Studies Conference, Abstracts, 2020)
In the introduction of the 2001 edition of The Great Transformation, Fred Block argues that we all have much to learn from the insights of Karl Polanyi. Relying on Polanyi’s arguments in the Great Transformation is not only useful in order to understand the history of market liberalism, but also for the contemporary debate on globalization and its contestation. The work of Karl Polanyi is inspiring a lot of academics nowadays who are studying the global uprisings since 2008. Some academics – like Block - argue that neoliberals embrace the same utopian visions of their predecessors which lead to counter-movements that are resisting marketization processes and its political and economic consequences. Relying on Polanyi’s work, I point to a danger of interpreting the current neoliberal order as a similar trend towards marketization as in the period that Polanyi is dealing with in his book. Misinterpreting the current marketization project raises questions not only about the feasibility of re-embedding the economy back into society, but also about the desirability of disembedding society from the economy. In concrete, I argue that the utopian character shifted from the marketization project to the counter-movements that are trying to resist and change it. This also raises questions about the role of social scientists in (studying) the process of social change in the twenty-first century.
Political Science; Global Studies
Keywords: contemporary relevance; countermovement; globalization; marketization; utopia